2002
DOI: 10.1159/000054730
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retinol-Binding Protein as a Prognostic Marker in Glomerulopathies

Abstract: Tubulointerstitial involvement seems to have a decisive influence on the progression of glomerular diseases. We have prospectively evaluated the levels of urinary retinol-binding protein (urRBP), a marker of proximal tubular dysfunction, in patients with different glomerulopathies (GPs) and correlated these levels with disease progression. By studying 238 patients with GPs, we found that urRBP tend to be lower in minimal change disease, glomerular hematuria and poststreptococcal glomerulonephritis as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Retinol-binding protein (RBP) is a low molecular weight protein (21 kDa) that transports retinol (vitamin A alcohol) from the liver to peripheral tissues. It passes freely through glomerular membranes and is reabsorbed by renal proximal tubules cells where it is catabolized, so an increase in the urinary excretion of RBP indicates proximal tubule injury and/or impaired proximal tubular function [ 57 , 58 ]. High levels of urine RBP suggest the presence of tubular injury in HIV-infected patients [ 31 ].…”
Section: Retinol Binding Proteinmentioning
confidence: 99%
“…Retinol-binding protein (RBP) is a low molecular weight protein (21 kDa) that transports retinol (vitamin A alcohol) from the liver to peripheral tissues. It passes freely through glomerular membranes and is reabsorbed by renal proximal tubules cells where it is catabolized, so an increase in the urinary excretion of RBP indicates proximal tubule injury and/or impaired proximal tubular function [ 57 , 58 ]. High levels of urine RBP suggest the presence of tubular injury in HIV-infected patients [ 31 ].…”
Section: Retinol Binding Proteinmentioning
confidence: 99%
“…Mastroianni Kirsztajn et al [18, 19] concluded that this biomarker reflects the occurrence of transitory or permanent tubulointerstitial dysfunction, and is a helpful tool for the follow-up of patients with GNs, making it possible to watch their progression to renal failure as well as their responsiveness to treatment, particularly in cases of idiopathic nephrotic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…As this parameter has been extensively studied at our institute [18,19,20], where an adequate method for determination of RBP has been developed [21,22,23], it will be analyzed here.…”
Section: Introductionmentioning
confidence: 99%
“…Even a slight impairment of the renal tubule can lead to increased urinary excretion of RBP. 40,41 Kuźniar et al 42 reported that an increase in urinary RBP excretion may be due to interstitial damage and not a decrease in the number of active nephrons. Such a conclusion was based on the lack of a correlation between RBP excretion and serum creatinine concentrations.…”
Section: Methodsmentioning
confidence: 99%